ANALISIS PENERAPAN AKUNTANSI MANAJEMEN LINGKUNGAN PADA PENGELOLAAN SAMPAH DI PT PERKEBUNAN NUSANTARA X PABRIK GULA MERITJAN - Nabila Dhiya Ulhaq; Nurafni Eltivia; Fathimatus Zahro Fazda Oktavia (Politeknik Negeri Malang, 2022)
This study was intended to investigate the implementation of Environmental Management Accounting (EMA) on waste management at PT Perkebunan Nusantara X Sugar Factory Meritjan Kediri East Java. This study was descriptive-qualitative, uses qualitative method and collects data by interviews and documentation from relevant parties, such as Financial and General Division and Engineering and Processing Division of PG Meritjan. PG Meritjan generates three types of waste, namely liquid, solid, air, and hazardous and toxic waste. EMA has two approaches, PEMA (Physical Environmental Management Accounting) and MEMA (Monetary Environmental Management Accounting). According to PEMA, PG Meritjan manage the Liquid waste by WWTP system, solid waste is managed by the Engineering and Processing Division to be reused and the rest is managed by a third party, air waste is managed by Dust Collector system, and hazardous and toxic waste is collected and managed by third party. In MEMA, PG Meritjan allocates environmental costs as Reconditioning and Environmental Management account but still be associated with a company's financial statements. This study suggests the company to make a separate financial report related with the waste cost allocation in order to inform the quality of waste management.